Lycopene and Garcinia cambogia Induce White-to-Brown Adipose Differentiation: An Innovative Strategy to Curb Obesity - Federica Mannino; Vincenzo Arcoraci; Giovanna Vermiglio; Davide Labellarte; Igor Pirrotta; Domenico Antonio Giorgi; Alessandro Scarfone; Alessandra Bitto; Letteria Minutoli; Mario Vaccaro; Mariarosaria Galeano; Giovanni Pallio; et al. (MDPI AG, 2024)
Obesity is considered one of the main risk factors for cardiovascular diseases. The browning process has been recently recognized as a promising anti-obesity therapy. Lycopene (LYC) and Garcinia cambogia fruit extract (GE) might be important resources for anti-obesity drugs; therefore, the aim of this study was to investigate the anti-obesity effects of LYC and GE on 3T3-L1 adipocytes and Zucker rats. Mouse 3T3-L1 pre-adipocytes were differentiated in mature adipocytes and then treated with LYC (0.5 μM), GE (30 mg/mL) or LYC + GE for 24 h. Moreover, male Zucker Crl:ZUC-Leprfa rats were randomly assigned to 5 groups of 10 animals to orally receive Vehicle (Ctrl), Orlistat (20 mg/kg), LYC (5 mg/kg), GE (1000 mg/kg) or LYC + GE for 28 days. LYC, GC extracts and even more LYC + GE stimulated the mRNA and protein expression of thermogenic genes UCP1, CIDEA and DIO2, significantly reduced lipid droplet size and increased lipid droplet number in adipocytes. UCP1 mRNA and protein expression was also increased in the visceral adipose tissue of the rats that received the dietary intake of LYC, GE and even more LYC + GE. Moreover, LYC + GE induced the reorganization of visceral fat depots that showed a great number of small adipocytes and a significant reduction in weight gain and food intake compared to the control group. The obtained results demonstrated that LYC + GE might be used as new approaches for obesity management in order to induce the browning process and achieve a metabolically active tissue instead of a tissue characterized by lipid depot accumulation.